Detection of Y chromosome microdeletions and mitochondrial DNA mutations in male infertility patients - (:unkn) unknown (FUNPEC-EDITORA, 2012)
Infertility affects about 10-15% of all couples attempting pregnancy with infertility attributed to the male partner in approximately half of the cases. Proposed causes of male infertility include sperm motility disturbances, Y chromosome microdeletions, chromosomal abnormalities, single gene mutations, and sperm mitochondrial DNA (mtDNA) rearrangements. To investigate the etiology of decreased sperm fertility and motility of sperm and to develop an appropriate therapeutic strategy, the molecular basis of these defects must be elucidated. In this study, we aimed to reveal the relationships between the genetic factors including sperm mtDNA mutations, Y chromosome microdeletions, and sperm parameters that can be regarded as candidate factors for male infertility. Thirty men with a history of infertility and 30 fertile men were recruited to the study. Y chromosome microdeletions were analyzed by multiplex PCR. Mitochondrial genes ATPase6, Cytb, and ND1, were amplified by PCR and then analyzed by direct sequencing. No Y chromosome microdeletions were detected in either group. However, a total of 38 different nucleotide substitutions were identified in the examined mitochondrial genes in both groups, all of which are statistically non-significant. Fifteen substitutions caused an amino acid change and 12 were considered novel mutations. As a conclusion, mtDNA mutations and Y chromosome microdeletions in male infertility should be examined in larger numbers in order to clarify the effect of genetic factors.
Keywords: Male infertility; Y chromosome microdeletion; mtDNA mutations; OXIDATIVE STRESS; SPERM MOTILITY; MEN; DELETIONS; ASSOCIATION; AZOOSPERMIA; ABSENCE